Oncostatin M promotes lipolysis in white adipocytes. (31st December 2022) - van Krieken, Pim P.; Roos, Julian; Fischer-Posovszky, Pamela; Wueest, Stephan; Konrad, Daniel
ABSTRACT: Oncostatin M (OSM) is a member of the glycoprotein 130 cytokine family that is involved in chronic inflammation and increased in adipose tissue under obesity and insulin resistance. OSM was shown to inhibit adipogenesis, suppress browning, and contribute to insulin resistance in cultured white adipocytes. In contrast, OSM may have a metabolically favourable role on adipocytes in mouse models of obesity and insulin resistance. However, a putative role of OSM in modulating lipolysis has not been investigated in detail to date. To address this, cultured white adipocytes of mouse or human origin were exposed to 10 or 100 ng/ml of OSM for various time periods. In murine 3T3-L1 cells, OSM stimulation directly activated hormone-sensitive lipase (HSL) and other players of the lipolytic machinery, and dose-dependently increased free fatty acid and glycerol release. In parallel, OSM attenuated insulin-mediated suppression of lipolysis and induced phosphorylation of serine-residues on the insulin receptor substrate-1 (IRS1) protein. Key experiments were verified in a second murine and a human adipocyte cell line. Inhibiton of extracellular signal-regulated kinase (ERK)-1/2 activation, abolished OSM-mediated HSL phosphorylation and lipolysis. In conclusion, OSM signalling directly promotes lipolysis in white adipocytes in an ERK1/2-dependent manner.